Simultaneous removal of ammonia and N-nitrosamine precursors from high ammonia water by zeolite and powdered activated carbon - Xue, Runmiao; Donovan, Ariel; Zhang, Haiting; Ma, Yinfa; Adams, Craig; Yang, John; Hua, Bin; Inniss, Enos; Eichholz, Todd; Shi, Honglan (Journal of environmental sciences (China), 2018)
When adding sufficient chlorine to achieve breakpoint chlorination to source water containing high concentration of ammonia during drinking water treatment, high concentrations of disinfection by-products（DBPs） may form. If N-nitrosamine precursors are present, highly toxic N-nitrosamines, primarily N-nitrosodimethylamine（NDMA）, may also form. Removing their precursors before disinfection should be a more effective way to minimize these DBPs formation. In this study, zeolites and activated carbon were examined for ammonia and N-nitrosamine precursor removal when incorporated into drinking water treatment processes.The test results indicate that Mordenite zeolite can remove ammonia and five of seven N-nitrosamine precursors efficiently by single step adsorption test. The practical applicability was evaluated by simulation of typical drinking water treatment processes using six-gang stirring system. The Mordenite zeolite was applied at the steps of lime softening, alum coagulation, and alum coagulation with powdered activated carbon（PAC） sorption. While the lime softening process resulted in poor zeolite performance, alum coagulation did not impact ammonia and N-nitrosamine precursor removal. During alum coagulation, more than67% ammonia and 70%–100% N-nitrosamine precursors were removed by Mordenite zeolite（except 3-（dimethylaminomethyl）indole（DMAI） and 4-dimethylaminoantipyrine（DMAP））. PAC effectively removed DMAI and DMAP when added during alum coagulation. A combination of the zeolite and PAC selected efficiently removed ammonia and all tested seven N-nitrosamine precursors（dimethylamine（DMA）, ethylmethylamine（EMA）, diethylamine（DEA）, dipropylamine（DPA）, trimethylamine（TMA）, DMAP, and DMAI） during the alum coagulation process.